Diarrhoea Complicating Severe Acute Malnutrition in Kenyan Children: A Prospective Descriptive Study of Risk Factors and Outcome - Talbert, Alison; Thuo, Nahashon; Karisa, Japhet; Chesaro, Charles; Ohuma, Eric; Ignas, James; Berkley, James A.; Toromo, Christopher; Atkinson, Sarah; Maitland, Kathryn (PLOS ONE, 2012)
Background Severe acute malnutrition (SAM) accounts for two million deaths worldwide annually. In those hospitalised with SAM, concomitant infections and diarrhoea are frequent complications resulting in adverse outcome. We examined the clinical and laboratory features on admission and outcome of children with SAM and diarrhoea at a Kenyan district hospital. Methods A 4-year prospective descriptive study involving 1,206 children aged 6 months to 12 years, hospitalized with SAM and managed in accordance with WHO guidelines. Data on clinical features, haematological, biochemical and microbiological findings for children with diarrhoea (≥3 watery stools/day) were systematically collected and analyzed to identify risk factors associated with poor outcome. Results At admission 592 children (49%) had diarrhoea of which 122 (21%) died compared to 72/614 (12%) deaths in those without diarrhoea at admission (Χ2 = 17.6 p<0.001). A further 187 (16%) children developed diarrhoea after 48 hours of admission and 33 died (18%). Any diarrhoea during admission resulted in a significantly higher mortality 161/852 (19%) than those uncomplicated by diarrhoea 33/351 (9%) (Χ2 = 16.6 p<0.001). Features associated with a fatal outcome in children presenting with diarrhoea included bacteraemia, hyponatraemia, low mid-upper arm circumference <10 cm, hypoxia, hypokalaemia and oedema. Bacteraemia had the highest risk of death (adjusted OR 6.1; 95% C.I 2.3, 16.3 p<0.001); and complicated 24 (20%) of fatalities. Positive HIV antibody status was more frequent in cases with diarrhoea at admission (23%) than those without (15%, Χ2 = 12.0 p = 0.001) but did not increase the risk of death in diarrhoea cases. Conclusion Children with SAM complicated by diarrhoea had a higher risk of death than those who did not have diarrhoea during their hospital stay. Further operational and clinical research is needed to reduce mortality in children with SAM in the given setting.